Clinical Value of 99Tcm-MDP SPECT Bone Scintigraphy in the Diagnosis of Unilateral Condylar Hyperplasia. (11th May 2014) - Wen, Bing; Shen, Ying; Wang, Chang-Yin
Abstract : Purpose . To investigate the clinical value of 99 Tc m -MDP SPECT for the diagnosis of unilateral condylar hyperplasia (UCH). Methods . One hundred forty-nine patients who underwent mandibular 99 Tc m -MDP SPECT between January 2009 and December 2012 were studied, including 105 cases that were clinically suspected of UCH and 44 comparable cases without UCH as a control group. Results . Increased bone activity was observed in the affected condyles for all UCH patients. In the UCH group, the relative percentage uptake on the affected side was 59% (S D ± 4.3 % ), significantly higher than the 41% (S D ± 4.1 % ) uptake on the contralateral side (P<0.001). Similarly, the condyle/skull ratio was significantly higher for the affected side (1.66 ± 0.63 ) than for the contralateral side (1.34 ± 0.34, P < 0.01 . No significant difference was found in the control group between the left and right condyles. Values for the sensitivity (95%), specificity (61%), positive (84.4%) and negative (84.6%) predictive values, and accuracy (84.5%) for 99 Tc m -MDP SPECT in the diagnosis of UCH were calculated. However, for the hyperplastic condyle, no correlation was observed between the thickness of each cartilage layer and the relative uptake in the SPECT image. Conclusion . 99 Tc m -MDP SPECT is accurate for diagnosing UCH and can provide a reference for treatment options.